Victimisation from Three Types of Intimate Partner Aggression and Mental Health Concomitants Among Women in Pakistan - Taalia Khan; Karin Österman; Kaj Björkqvist (Journal of Educational, Health and Community Psychology, 2019)
The aim of the study was to compare associations between three types of female victimization from intimatepartner aggression (IPA) and their mental health concomitants. A questionnaire was completed by 569 relatively well-educated women in Pakistan (97.3% had at least a Bachelor’s degree). The mean age was 31.4 years (SD 9.1), and the age range was between 18 and 70 years. The questionnaire included scales for measuring victimization from physical aggression, verbal aggression, and indirect aggressive social manipulation perpetrated by the husband against the wife, and four subscales from the Brief Symptom Inventory (BSI): depression, anxiety, obsessive-compulsive symptoms, and somatization. Victimization from verbal aggression was the most common type, followed by indirect aggression, while physical aggression was the least common. All three types of IPA were significantly associated with all four BSI subscales and most strongly with indirect aggression, while physical aggression showed the weakest associations. Keywords: Intimate partner aggression, physical, verbal, indirect, mental health, Pakistan